Modulator Demodulator In Phase Quadrature Dengan Pembawa Frekuensi 50 MHz Berbasis Komponen Diskrit - Suharno Suharno; Masbah R.T. Siregar; Taswanda Taryo; Kun Wardana (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2023)
ABSTRACT One of the most important parts of a linear accelerator is the RF System. Two different input signals can produce distortion which can cause problems in intermodulation. Effect of RF power performance on noise as well as performance evaluation so as to produce a clear and strong signal without significant distortion or transmission loss.The Inphase quadrature analog modulator demodulator can achievec with 900 phase shit signal to I and Q inputs, the carrier signal using a variable oscillator or VCO with a single 50 MHz output. 16 Bit of ADC and DAC module optimized as input or output with I/Q analog modulator demodulator. In this paper, ADISIM RF simulation is used to display the results of the RF system design, with two parameters namely Spurios Free Dynamic Range) and IMD (Two Tone Intermodulation Distortion) for Transmitter and one parameter namely Noise Figure (NF) for Receiver. Keywords : I/Q Modulator Demoduator, ADISIM RF, SFDR, IMD, NF